2019
DOI: 10.14412/2074-2711-2019-3-43-46
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial genome and risk of multiple sclerosis

Abstract: Mitochondrial DNA (mtDNA) polymorphism makes a certain contribution to the formation of a genetic risk of multiple sclerosis (MS).Objective: to analyze the frequency of mtDNA variants in patients with MS and control individuals in the Russian population. A similar study was conducted for the first time.Patients and methods. The polymorphism of mtDNA was studied in the Russian population: in 283 unrelated patients with relapsing-remitting MS and in 290 unrelated healthy controls matched for gender and age.Resul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 41 publications
0
4
0
Order By: Relevance
“…Caucasians [42] and a significant association with MS in Russian [27,28], Persian [29] and Bulgarian [30] patients. Results from this study also revealed the presence of haplogroup T in MS patients only.…”
Section: Plos Onementioning
confidence: 90%
See 3 more Smart Citations
“…Caucasians [42] and a significant association with MS in Russian [27,28], Persian [29] and Bulgarian [30] patients. Results from this study also revealed the presence of haplogroup T in MS patients only.…”
Section: Plos Onementioning
confidence: 90%
“…We also did not observe a significant difference in the frequency of haplogroup J between patients and controls. An earlier study by Reynier et al, [ 43 ] found haplogroup J only in MS patients with optic neuritis (ON) but not in MS patients without visual symptoms, and suggested that this haplogroup might constitute a risk factor for ON occurrence when it is coincidentally associated with MS, but not as a risk factor for developing MS. On the other hand, other studies have revealed a moderate effect of haplogroup J with MS susceptibility in Caucasians [ 42 ] and a significant association with MS in Russian [ 27 , 28 ], Persian [ 29 ] and Bulgarian [ 30 ] patients. Results from this study also revealed the presence of haplogroup T in MS patients only.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations